فعالية إستخدام طريقة الإملاء في ترقية مهارة الكتابة لطلاب الصف العاشر في معهد التربية الإسلامية دار الأيتام الصافي سيليونغسي - Miftah Huljanah; Tahir Wijaya (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2025)
This research is based on observation data which shows that students have difficulty writing Arabic due to differences in intellectual abilities and different school backgrounds. In response to this problem, the researcher conducted a quasi-experimental study. This research aims to: 1) To find out students' ability in writing skills in tenth grade at Daarul Aytam As-Shofy Cileungsi Islamic Boarding School. 2) To find out the effectiveness of using the Imla' simak method in improving writing skills in tenth grade at Daarul Aytam As-Shofy Cileungsi Islamic Boarding School. This research is a quantitative research. Using quasi-experimental method in the research. The data collection methods used were observation, documentation, pretest and posttest. The data analysis method used was the t-test. This is evidenced by the increase in the pre-test score. Before using the Imla' method, students obtained a pre-test score of 73.00 with a sufficient category, and after using the Imla' method, the post-test score was 86.00 with a very good category. Evidenced by the results of the t-test calculation which produces a calculated t value greater than the t table value, namely 6.475 and based on a significant value (2-tailed) of 0.000 which is smaller than 0.05. The accepted hypothesis is the alternative hypothesis (Ha) and the rejected hypothesis is the first hypothesis (H0).